2020
DOI: 10.1155/2020/8888270
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Aspergillus and Cryptococcus in Immunocompromised Host: A Case Report and Review of Literature

Abstract: Management of infections in the immunocompromised patient requires unique considerations that are not typically seen in the immunocompetent. Immunocompromised hosts require a broad set of differential diagnoses when presenting with febrile illness involving a wide variety of microbiology. Moreover, fungal infections are common, and cotreatment of fungal and bacterial infections occurs with regularity. Fungal coinfection, however, is rare. Here, we describe a patient with Aspergillus and recurrent Cryptococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Pneumocystis jiroveci is also one of the most common pathogens in immunosuppressed hosts (Azoulay et al, 2019). However, the mixed mycoses reported in the literature are mainly mixed infections of Aspergillus and Cryptococcus (Lin et al, 2006;Enoki et al, 2012;Wang et al, 2018;Awari et al, 2020). There have also been reports of Aspergillus and Mucor coinfection in the lung or outside the lungs (Bergantim et al, 2013;Mahadevaiah et al, 2013;Webb et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pneumocystis jiroveci is also one of the most common pathogens in immunosuppressed hosts (Azoulay et al, 2019). However, the mixed mycoses reported in the literature are mainly mixed infections of Aspergillus and Cryptococcus (Lin et al, 2006;Enoki et al, 2012;Wang et al, 2018;Awari et al, 2020). There have also been reports of Aspergillus and Mucor coinfection in the lung or outside the lungs (Bergantim et al, 2013;Mahadevaiah et al, 2013;Webb et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The morphological similarity of mold makes pathological diagnosis dependent on experienced technicians. Awari et al and Wang et al reported some cases of mixed mycoses of Aspergillus and Cryptococcus in both immunocompromised and immunocompetent patients (Wang et al, 2018;Awari et al, 2020). Coinfection with Talaromyces marneffei and Cryptococcus neoformans has also been reported in a non-HIV patient (He et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other causes contributing to the recurrence of pulmonary cryptococcosis include immunocompromised status, suboptimal therapy, and economic challenges. [ 19 , 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Other causes contributing to the recurrence of pulmonary cryptococcosis include immunocompromised status, suboptimal therapy, and economic challenges. [19,20] The precise diagnosis of a disease is paramount to successful treatment. Without an accurate diagnosis, an appropriate treatment cannot be initiated.…”
Section: Discussionmentioning
confidence: 99%